EFFECTS OF POLYVINYL ALCOHOL ON THE CHARACTERISTICS OF BIOPLASTICS MADE FROM COMPOSITES OF STARCH?ETHYL LAURATE COMPLEXES AND XANTHAN GUM - Rafi Ning Sinatriyo, Khaidir
Conventional petroleum-based plastics are difficult to decompose naturally and cause environmental pollution. Developing bioplastic is one of the alternative solutions to overcome those problems. Starch is one of bioplastic material, which is economical, abundant in nature, non-toxic, and biodegradable. In this study, plastics were made from starch-ethyl laurate, polyvinyl alcohol, and xanthan gum (PEL?PX) composites. Ethyl laurate, a fatty acid derivative with a hydrophobic aliphatic chain, can be complexed with starch to increase the tensile strength of the resulting plastics by increasing its crystallinity. Polyvinyl alcohol (PVA) and xanthan gum are used as the additive polymers to improve the elasticity and tensile strength of the plastics. The complexes were prepared by mixing starch and ethyl laurate at different concentrations of 3, 5, 7, and 10% (w/w based on the mass of complex) at 86 °C. The complexes were then directly mixed with 10% xanthan gum (w/w based on the total composite mass) and PVA with varying molecular weights of 145, 72, and 30 kDa. The mass ratios of PEL and PVA were varied at 3:1, 2:1, and 1:1. The mixture was then blended with plasticizers such as 20% glycerol and 10% PEG?200 (w/w based on the total composite mass). Based on the FTIR spectrum, the peak of ethyl laurate did not appear in the spectrum of the starch composite plastic. This indicated the formation of an inclusion complex where ethyl laurate reside inside the cavity of single helixes of amylose molecules. Contact angle measurements showed a range of contact angle values of 15.65?35.08°, indicating that the plastics were hydrophilic. The finding were supported by microscope images showing plastic swelling after the plastics were dipped in an iodine solution, indicating that the composite plastics readily bound water. The composition that produced the highest mechanical properties was PEL 5%?PX 145 (1:1) plastic with tensile strength and elongation of 4.03±1.37 MPa and 86.88±8.59%, respectively. These mechanical properties demonstrate the potential of this bioplastic for various applications such as coffee capsule, compostable plastic bag, and lightweight product packaging.